Role of ATP as a Key Signaling Molecule Mediating Radiation-Induced Biological Effects - Shuji Kojima; Yasuhiro Ohshima; Hiroko Nakatsukasa; Mitsutoshi Tsukimoto (SAGE Publishing, 2017)
Adenosine triphosphate (ATP) serves as a signaling molecule for adaptive responses to a variety of cytotoxic agents and plays an important role in mediating the radiation stress-induced responses that serve to mitigate or repair the injurious effects of γ radiation on the body. Indeed, low doses of radiation may have a net beneficial effect by activating a variety of protective mechanisms, including antitumor immune responses. On the other hand, ATP signaling may be involved in the radiation resistance of cancer cells. Here, focusing on our previous work, we review the evidence that low-dose γ irradiation (0.25-0.5 Gy) induces release of extracellular ATP, and that the released ATP mediates multiple radiation-induced responses, including increased intracellular antioxidant synthesis, cell-mediated immune responses, induction of DNA damage repair systems, and differentiation of regulatory T cells.